Development of an Experimental Model to Study the Relationship Between Day-to-Day Variability in Blood Pressure and Aortic Stiffness - Bouissou-Schurtz, Camille; Lindesay, Georges; Regnault, Véronique; Renet, Sophie; Safar, Michel E.; Molinie, Vincent; Dabire, Hubert; Bezie, Yvonnick (Frontiers in Physiology, 2015)
We aimed to develop an animal model of long-term blood pressure variability (BPV) and to investigate its consequences on aortic damage. We hypothesized that day-to-day BPV produced by discontinuous treatment of spontaneously hypertensive rats (SHR) by valsartan may increase arterial stiffness. For that purpose, rats were discontinuously treated, 2 days a week, or continuously treated by valsartan (30 mg/kg/d in chow) or placebo. Telemetered BP was recorded during 2 minutes every 15 min, 3 days a week during 8 weeks to cover the full BP variations in response to the treatment schedule. Pulse wave velocity (PWV) and aortic structure evaluated by immunohistochemistry were investigated in a second set of rats treated under the same conditions. Continuous treatment with valsartan reduced systolic BP (SBP) and reversed the aortic structural alterations observed in placebo treated SHR (decrease of medial cross-sectional area). Discontinuous treatment with valsartan decreased SBP to a similar extent but increased the day-to-day blood pressure variability, short term BPV, diastolic blood pressure (DBP) and PWV as compared with continuous treatment. Despite no modifications in the elastin/collagen ratio and aortic thickness, an increase in PWV was observed following discontinuous treatment and was associated with a specific accumulation of fibronectin and its av-integrin receptor compared with both groups of rats. Taken together the present results indicate that a discontinuous treatment with valsartan is able to induce a significant increase in day-to-day blood pressure variability coupled to an aortic phenotype close to that observed in hypertension. This experimental model should pave the way for future experimental and clinical studies aimed at assessing how long-term BPV increases aortic stiffness.